(untitled) (Journal of Renal and Hepatic Disorders, 2023)
Hepatocellular carcinoma (HCC) is one of the commonest causes of cancer-related morbidity and mortality worldwide. However, only a limited number of studies on HCC have been conducted in Tanzania. We therefore conducted a cross-sectional study among in-patients treated for HCC in a tertiary referral hospital located in Dar es Salaam, Tanzania, in order to provide a concise description of the clinical characteristics and treatment options offered in the study setting. We identified 36 in-patients treated for HCC over a 6-month data collection period. Seventy-seven percent (n = 28) of the participants were males and about two-thirds (61.2%) were aged between 40 and 60 years. Majority (44.4% [n = 16]) of the patients had Child-Pugh class B and an Eastern Cooperative Oncology Group (ECOG) performance status of 2 (33.3% [n = 12]). Patients with tumors >6.5 cm and multinodular tumors (>3 nodules) accounted for 69.4% (n = 25) and 55.6% (n = 20), respectively. Portal vascular invasion and extrahepatic metastasis were respectively present in 27.8% (n = 10) and 25% (n = 9) of the patients. Of the study participants, only two had early-stage disease as per the Barcelona Clinic Liver Cancer (BCLC) staging system, corresponding to the observed tumor resection rate of 5.6%. The most frequently reported inoperable factor among the study participants was an ECOG performance status > 0 (n = 30 [83.3%]). Findings thus reveal a high proportion of late-stage diseases among participants that could have resulted in the observed low tumor resection rate. Initiatives to facilitate identification of the disease at an early stage are therefore paramount in optimizing care.